2019
DOI: 10.3390/ijms20143471
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 Promotes the Tumorigenic Phenotype in KGN, a Human Granulosa Cell Tumor-Derived Cell Line

Abstract: Granulosa cell tumors of the ovary (GCT) are the predominant type of ovarian sex cord/stromal tumor. Although prognosis is generally favorable, the outcome for advanced and recurrent GCT is poor. A better understanding of the molecular pathogenesis of GCT is critical to developing effective therapeutic strategies. Here we have examined the potential role of the runt-related transcription factor RUNX3. There are only two GCT cell lines available. While RUNX3 is silenced in the GCT cell line KGN cells, it is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Recently it has been demonstrated that RUNX3 when associates with MYC functions as a tumor promoter whereas; acts as a tumor suppressor when interacts with p53 [47]. Various other studies have demonstrated the oncogenic role of RUNX3 [46,[48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been demonstrated that RUNX3 when associates with MYC functions as a tumor promoter whereas; acts as a tumor suppressor when interacts with p53 [47]. Various other studies have demonstrated the oncogenic role of RUNX3 [46,[48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The classification of COV434 as a GCT-derived cell line has been questioned. Recent studies show that this cell line was likely derived from a small-cell carcinoma of the ovary hypercalcemic-type (SCCOHT) [105][106][107]. The cell of origin of these tumors is unknown, with reports postulating they are likely derived from the germ cells [108].…”
Section: Gct-derived Cell Linesmentioning
confidence: 99%
“…SCCOHT are characterized by the loss of both SMARCA2 and SMARCA4, which are also not expressed in COV434 cells [105,107]. Moreover, the lack of expression of RUNX2 and high expression of RUNX3 in COV434 suggests that these cells do not represent primary jGCT [106]. Noticeably, the study of Karnezis et al indicates that COV434 cell line has all morphological, immunohistochemical, genetic and clinical Genetics and Mutational Landscape of Ovarian Sex Cord-Stromal Tumors DOI: http://dx.doi.org/10.5772/intechopen.97540 characteristics of SCCOHT [107].…”
Section: Gct-derived Cell Linesmentioning
confidence: 99%
“…Loss of Runx3 expression has also frequently been found in melanoma cells as compared to melanocytes, and there is a good negative correlation between Runx3 expression and melanoma malignancy [ 40 ]. In addition, many functional studies have demonstrated that Runx3 is a tumor suppressor in many types of cancers but is a tumor promoter in other types [ 37 , 38 , 39 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%